2006
DOI: 10.5194/nhess-6-697-2006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced radar precipitation estimates using a combined clutter and beam blockage correction technique

Abstract: Abstract. Weather radar observations are currently the most reliable method for remote sensing of precipitation. However, a number of factors affect the quality of radar observations and may limit seriously automated quantitative applications of radar precipitation estimates such as those required in Numerical Weather Prediction (NWP) data assimilation or in hydrological models. In this paper, a technique to correct two different problems typically present in radar data is presented and evaluated. The aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…In literature, multiple GC identification techniques have been proposed, using either pulse to pulse reflectivity fluctuations [ Wessels and Beekhuis , 1994], radial Doppler velocity information [ Joss and Lee , 1995], spatial reflectivity information [ Alberoni et al , 2001], or dual‐polarization data [ Giuli et al , 1991]. Other sources of data have also been used to identify GC, such as digital elevation models, temperature, or satellite information [e.g., Delrieu et al , 1995; Michelson and Sunhede , 2004; Fornasiero et al , 2006]. Currently, most GC identification algorithms make use of a classification scheme using multiple information criteria [e.g., Joss and Pittini , 1991; Joss and Lee , 1995; Steiner and Smith , 2002; Grecu and Krajewski , 2000; Berenguer et al , 2006; Cho et al , 2006].…”
Section: Radar Reflectivity Analysismentioning
confidence: 99%
“…In literature, multiple GC identification techniques have been proposed, using either pulse to pulse reflectivity fluctuations [ Wessels and Beekhuis , 1994], radial Doppler velocity information [ Joss and Lee , 1995], spatial reflectivity information [ Alberoni et al , 2001], or dual‐polarization data [ Giuli et al , 1991]. Other sources of data have also been used to identify GC, such as digital elevation models, temperature, or satellite information [e.g., Delrieu et al , 1995; Michelson and Sunhede , 2004; Fornasiero et al , 2006]. Currently, most GC identification algorithms make use of a classification scheme using multiple information criteria [e.g., Joss and Pittini , 1991; Joss and Lee , 1995; Steiner and Smith , 2002; Grecu and Krajewski , 2000; Berenguer et al , 2006; Cho et al , 2006].…”
Section: Radar Reflectivity Analysismentioning
confidence: 99%
“…Then, a 2D dynamic map is constructed for each pixel, taking into account the beam trajectory simulated using the vertical profiles from radio soundings. By adopting these information, the mean clutter should be avoided and the beam blockage reduced to values lower than 50 % (Bech et al 2003;Fornasiero 2006;Fornasiero et al 2006).…”
Section: Radarmentioning
confidence: 99%
“…However, various studies have revealed that estimating precipitation from radar also poses significant problems; electronic miscalibration (Goudenhoofdt and Delobbe, 2009), signal contamination by non-meteorological echoes or range effect (Fries et al, 2014), beam blocking by natural impediments (e.g. mountain region, surrounding hills with similar or higher altitudes) and the variance in the reflectivity and rainfall rate relationships (Jameson and Kostinski, 2002;Fornasiero et al, 2006;Vulpiani et al, 2012;Yoon and Bae, 2013;Lim et al, 2014;Qin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%